The Biological Effect of Contralateral Forepaw Stimulation in Rat Focal Cerebral Ischemia: A Multispectral Optical Imaging Study - Luckl, Janos; Baker, Wesley; Sun, Zheng-hui; Durduran, Turgut; Yodh, Arjun G.; Greenberg, Joel H. (Frontiers in Neuroenergetics, 2010)
Our group has already published the possible neuroprotective effect of contralateral forepaw stimulation in temporary focal ischemia in a study. However, the background is still unclear. In the present study we investigated the possible mechanism by monitoring focal ischemia with multispectral [laser speckle, imaging of intrinsic signals (OIS)] imaging. Sprague–Dawley rats were prepared using 1.2% isoflurane anesthesia. The middle cerebral artery was occluded by photothrombosis (4 mW) and the common carotid artery was ligated permanently. Physiological variables were constantly monitored during the experiment. A 6 × 6 mm area centered 3 mm posterior and 4 mm lateral to Bregma was thinned for laser speckle and OIS imaging. Nine circular regions of interests (0.3 mm in diameter) were evenly spaced on the speckle contrast image for the analysis of peri-infarct flow transients, blood flow, and metabolic changes. Both the sham (n = 7) and forepaw-stimulated animals (n = 7) underwent neurological examinations 24 h after ischemia at which point all animals were sacrificed and the infarct size was determined by triphenyltetrazolium chloride. The physiological variables were in normal range and the experimental protocol did not cause significant differences between groups. Both the neurological scores (sham: 3.6 ± 1.7, stimulated: 4.3 ± 1.4) and the infarct volume (sham: 124 ± 39 mm3, stimulated: 147 ± 47 mm3) did not show significant differences between groups. The forepaw stimulation did not increase the intra-ischemic flow neither over the penumbral or the peri-ischemic area. However, the hemoglobin transients related metabolic load (CMRO2) was significantly lower (p < 0.001) while the averaged number of hyperemic flow transients were significantly (p = 0.013) higher in the forepaw (sham: 3.5 ± 2.2, stimulated: 7.0 ± 2.3) stimulated animals.